Komposisi Nuklotida Sekuen Gen rbcL pada Kappaphycus alvarezii yang dibudidaya di Jawa Timur - Alin Asyabil; Yenny Risjani; Lawrence M. Liao (Jurnal Penelitian Pendidikan IPA, 2023)
Kappaphycus alvarezii seaweed is an important fishery commodity in Indonesia because it contains carrageenan, an important main ingredient in various industries. Research on the genetic characterization of seaweed in Indonesia is important as a source of information and genetic data needed to develop aquaculture practices such as breeding programs. Therefore, this study was conducted to determine the nucleotide composition of the rbcL gene sequence in Kappaphycus alvarezii as part of a genetic characterization study of Kappaphycus alvarezii seaweed in East Java. This study used five samples taken in Banyuwangi, Situbondo and Sumenep and compared them with the Kappaphycus alvarezii seaweed database at GenBank. The method used was the PCR method, and the primer pairs used were F-577 5'-GTATATGAAGGTCTAAAAGGTGG-3' and R-753 5'-GCTCTTTCATACATATCTTCC-3'. Based on research, primers F-577 and R-753 succeeded in amplifying the rbcL gene in Kappaphycus alvarezii samples in a partial manner with a length of 295 – 299 bp. The DNA sequence results of the sample have a similarity of 100% to the database in GeneBank. Nucleotide composition analysis shows the existence of genetic variations in the DNA sequences studied.